2012
DOI: 10.3109/0142159x.2012.687479
|View full text |Cite
|
Sign up to set email alerts
|

Deliberative curriculum inquiry for integration in an MD curriculum: Dalhousie University's curriculum renewal process

Abstract: Background: Dalhousie University's MD Programme faced a one-year timeline for renewal of its undergraduate curriculum. Aim: Key goals were renewed faculty engagement for ongoing quality improvement and increased collaboration across disciplines for an integrated curriculum, with the goal of preparing physicians for practice in the twenty-first century. Methods: We engaged approximately 600 faculty members, students, staff and stakeholders external to the faculty of medicine in a process described by Harris (19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Such activities bridge the gap between the Medical Education Unit and the departments and can be of great help in facilitating tasks to be accomplished and during the ongoing revision and maintenance of the program. The Medical Education Unit should establish a system for rewarding academics and clinicians who have played a role in the development and maintenance of the new curriculum and should regularly invest in building such bridges with academics (Reid et al 2012).…”
Section: Tipmentioning
confidence: 99%
“…Such activities bridge the gap between the Medical Education Unit and the departments and can be of great help in facilitating tasks to be accomplished and during the ongoing revision and maintenance of the program. The Medical Education Unit should establish a system for rewarding academics and clinicians who have played a role in the development and maintenance of the new curriculum and should regularly invest in building such bridges with academics (Reid et al 2012).…”
Section: Tipmentioning
confidence: 99%
“…This process allowed for clear development of curriculum priorities based on multiple professional and interdisciplinary perspectives. This process of curricular design has been previously described as part of a process of deliberative curriculum inquiry where it was shown to “create shared frameworks and foster collaboration” (Reid et al, 2012, p. e789). Sharing content expertise as well as previous professional experiences was an important part of designing other interprofessional web-based education resources (Lax et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Several articles argued for elaborate, mixed-method, sequential studies to avoid the limitations of expert opinion or consensus processes, or else suggested a practice-based needs assessment [22][23][24]. For example, Gonsalves et al conducted an initial survey phase, followed by a limited practice-based audit of clinical skills to identify curricular topics, then a focus group process phase, followed by a modified Delphi survey to achieve consensus [22].…”
Section: ) the Manualmentioning
confidence: 99%
“…Making change to curriculum that is inclusive and effective can be challenging given limited researcher resources. A paper outlining a rapid (one-year) curriculum renewal by deliberative inquiry, recommended that "members of purposefully constituted groups reach curriculum decisions through processes of deliberation" [24]. Concepts from Reid et al that are relevant to the current NADA project included: parallel processes that engage relevant stakeholders, iterative work/design teams, and the use of technology via blogs and other web-based update systems.…”
Section: ) the Manualmentioning
confidence: 99%
See 1 more Smart Citation